Modernization of Territorial Organization of Power in Regional Development Context - Cherniak , Mykhailo (Theory and Practice of Public Administration, 2019)
Transformation of the state that includes a transfer from traditional public administration to governance is going on in many countries, in particular those with transition economy, which proves the topicality and importance of studying the issues of changes in territorial organization of power. The objective of the present paper is substantiation of the lines of modernizing the territorial organization of power in the context of regional development with account of the current changes in the country’s socio-economic condition. An effective public administration is considered to be one of the basic factors underlying the success of the regions, since it provides training of qualified administrative personnel, technological transformations, support of the natural and artificial environment, and expansion of “non-specialized interconnections” that involve the labor market, government institutions, social norms and values. The institutions at the territorial level should be regarded as a necessary component of the ascendant forms of regional policy under the conditions when regional development is getting increasingly more dependent on the global processes. Such a change of conditions makes the regions cater for their own development using their own resources. Thus, the role of the territorial bodies of power has shifted from territorial management of the state policy, aimed at redistribution of social benefits, towards “entrepreneurship”, when the regions compete with each other. Accordingly, the target reference points have changed from the policy aiming to overcome inter-regional inequality to the one oriented to develop and enhance the competitive capacity of the regions. With regard to the above said, the paper indicates the main characteristics of a traditional hierarchical approach as well as those of a new ascendant approach to regional development. It has been proved that multilevel governance should become the basis for the modernization of territorial organization of power in order to provide an effective regional development. An approach of this kind is a tool for preventing the realization of destructive forms of competition between the territories which try to provide their own development at the expense of others.